2021
DOI: 10.1042/bsr20200776
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of miRNA–mRNA network in high altitude retinopathy by bioinformatics analysis

Abstract: High-altitude retinopathy (HAR) is an ocular manifestation of acute oxygen deficiency at high altitudes. Although the pathophysiology of HAR has been revealed by many studies in recent years, the molecular mechanism is not yet clear. Our study aimed to systematically identify the genes and microRNA (miRNA) and explore the potential biomarkers associated with HAR by integrated bioinformatics analysis. The mRNA and miRNA expression profiles were obtained from the Gene Expression Omnibus database. We performed Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Abnormal VEGF and disrupted angiogenesis are described in lung tissues of infants that died of severe BPD [64]. In addition, miR-1255b-5p is downregulated in hypoxia-induced lung A549 cells [65] as well as in models of high altitude retinopathy [66], and colorectal cancer, where it also regulates telomerase activity and suppresses EMT [67]. Notably, hypoxic stress in the presence of hyperoxia results in altering alveologenesis in mouse models of neonatal BPD [68].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal VEGF and disrupted angiogenesis are described in lung tissues of infants that died of severe BPD [64]. In addition, miR-1255b-5p is downregulated in hypoxia-induced lung A549 cells [65] as well as in models of high altitude retinopathy [66], and colorectal cancer, where it also regulates telomerase activity and suppresses EMT [67]. Notably, hypoxic stress in the presence of hyperoxia results in altering alveologenesis in mouse models of neonatal BPD [68].…”
Section: Discussionmentioning
confidence: 99%
“…The DAVID software ( ; accessed on 1 March 2022) was used for GO and KEGG enrichment analyses of pyroptosis-related DEGs [ 22 ]. The DEGs were characterized, and key pathways were examined.…”
Section: Methodsmentioning
confidence: 99%
“…We mainly focused on the two miRNAs (miR-424 and miR-346) whose expression was significantly up-regulated with the increase of high glucose concentration. Previous studies have reported the involvement of miR-424 in retina-associated diseases [35][36] , while miR-346 has not been investigated yet. Therefore, miR-346 was selected for further investigations.…”
Section: Expression Of Mirnas In Human Retinal Pigmentmentioning
confidence: 99%